2011
DOI: 10.1128/jb.00083-11
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Streptococcus suis Serotype 14 Strain JS14

Abstract: Streptococcus suis is an important zoonotic agent leading to a variety of diseases in swine and can be transmitted to human beings upon close contact. Here, we report the complete genome sequence of S. suis serotype 14 strain JS14 which was isolated from a diseased pig in Jiangsu Province, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…b Data are from assays using tetracycline (10 g/ml) for resistance selection, but closely comparable results were obtained using erythromycin (10 g/ml). (16,25). The tandem presence of a ribosomal protection tet gene and an efflux tet gene is consistent with the high-level tetracycline resistance displayed by S. suis 32457 and the transconjugants.…”
Section: Evidence Of a 50-to 60-kb Mobile Element Carrying Tet(o/w/ 3mentioning
confidence: 54%
“…b Data are from assays using tetracycline (10 g/ml) for resistance selection, but closely comparable results were obtained using erythromycin (10 g/ml). (16,25). The tandem presence of a ribosomal protection tet gene and an efflux tet gene is consistent with the high-level tetracycline resistance displayed by S. suis 32457 and the transconjugants.…”
Section: Evidence Of a 50-to 60-kb Mobile Element Carrying Tet(o/w/ 3mentioning
confidence: 54%
“…A correlation was tentatively established between the CPS structure determined in this study and 7 genes encoding putative glycosyltransferases and a polymerase, which are clustered in the S. suis serotype 14 cps locus (Hu et al 2011;Wang et al 2011) (see Supplementary data Table S1 and Fig. 5).…”
Section: Biosynthesis Of the Capsular Polysaccharidementioning
confidence: 96%
“…Sialic acid has been shown to be an important virulence factor for other meningitis-causing bacteria (Severi et al 2007). The complete genome sequence of this serotype has recently been published (Hu et al 2011). We report here for the first time the structure determination of S. suis serotype 14 CPS using chemical, chromatographic, and spectroscopic methods.…”
Section: Introductionmentioning
confidence: 98%
“…In serotypes 6,11,12,13,15,17,18,20,21,22,24,27,28,29,30, and 31, partial sequences of the cps gene clusters (orfY-cpsD genes) have been determined and deposited in the GenBank database (accession numbers JF791152 to JF791167). Furthermore, complete genome sequences of 13 S. suis nonreference strains (seven of serotype 2 and one of serotypes 1, 1/2, 3, 7, 9, and 14) have been determined to date (19)(20)(21)(22)(23)(24). A previous study analyzing 15 S. suis cps gene clusters indicated that all the cps gene clusters are located between the orfZ (conserved hypothetical protein gene) and aroA (3-phosphoshikimate 1-carboxyvinyltransferase gene) genes on the chromosome.…”
mentioning
confidence: 99%